PENGARUH MEDIA SOSIAL DAN STATUS SOSIAL EKONOMI TERHADAP PERILAKU KONSUMTIF SISWA KELAS XI IPS SMA NEGERI I GUBUG - Dewi Larasati; Efriyani Sumastuti; Dwi Prastiyo Hadi; Mahmud Yunus (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2020)
ABTRACT This study aims to determine the effect of the use of social media and socioeconomic status on the consumer behavior of class XI IPS students of SMA Negeri 1 Gubug both commercially and simultaneously. the population in this study was 106 students with a sample of 84 students. This study uses a quantitative approach. The results of this study were obtained Y = -8,890 + 0,855X1 + 0,606X2. Social media simultaneously has a positive and significant effect on consumptive behavior in XI IPS students of SMA Negeri 1 Gubug. Socio-economic status has a positive and significant influence on the consumptive behavior of SMA Negeri 1 Gubug students. Partially, social media and socioeconomic status influence consumer behavior by 0.527 meaning that the contribution of variable X (independent) is social media and socioeconomic status to the Y variable (dependent) consumer behavior is 52.7% while the remaining 47.3 % is influenced by other variables.